Determinants of renewable energy consumption in ten developing countries / Farah Wahida Abu Supian - Abu Supian, Farah Wahida (Faculty of Business and Management, 2020)
This study aims to investigate the relationship of between the Energy Use, Gross Domestic Product (GDP), Carbon Emissions (CO2), Corruption Perception Index and Population to the Renewable Energy Consumption in 10 selected developing countries which are Argentina, Bangladesh, China, India, Indonesia, Malaysia, Mexico, Pakistan, Philippines, and Thailand. The study has used Panel Regression Model to discover the relationship between Energy Use, Gross Domestic Product (GDP), Carbon Emissions (CO2), Corruption Perception Index, Population and Renewable Energy Consumption. The annual percentage of each variable starting from 2001 – 2014 is gathered to run the test in this study. Based on the result, Corruption Perception Index and Population have a significant positive relationship toward Renewable Energy Consumption, Gross Domestic Product and Carbon Emissions (CO2) have a significant negative relationship toward Renewable Energy Consumption, while, Energy Use has insignificant positive relationship toward Renewable Energy Consumption in 10 selected developing countries which are Argentina, Bangladesh, China, India, Indonesia, Malaysia, Mexico, Pakistan, Philippines, and Thailand. This shows that Renewable Energy Consumption is sensitive to changes in all the independent variables except for Energy Use. Furthermore, based on the result, the Corruption Perception Index and Population are the most significant determinant affecting renewable energy consumption.